Perceptions of educational environment among medical students of University Tunku Abdul Rahman: A cross sectional study / Kye Mon Min Swe - Kye Mon, Min Swe (2019)
Educational environment of an education institution is where teaching and learning activities occur and it is a major determinant of developing motivation in students for their effective learning. Educational environment plays an important role in academic achievements, satisfaction and successes of students. Objectives of the research study were to determine the perceptions of educational environment among medical students of University Tunku Abdul Rahman (UTAR) and to compare perceptions of educational environment between pre-clinical and clinical year students. This study was a cross-sectional study involving all the medical students (year 1 to year 5). Dundee Ready Educational Environment Measure (DREEM) was used to determine the educational environment of medical students of UTAR. Data was analyzed by using SPSS. Twohundred-and-seven (n=207) students responded to the questionnaires. Amongst the respondents, 63.3% were female students, while 70.0% of them were between 21-25 years of age. There were 79 or 38.2% students studying in the preclinical phase (year 1 to year 2) while 128 or 61.8% were studying in the clinical phase (year 3 to year 5). Perceptions of medical students on educational environment of UTAR showed that there were more positive than negative aspects (M=123.41, SD =17.09). Highest rated item was item 2; “The teachers are knowledgeable” (M= 3.43) and lowest rated item was item 27; “I am able to memorize all I need” (M= 1.27). Meanwhile, upon comparison, pre-clinical year students were more satisfied than clinical year students did in all the five domains of DREEM. In addition, student’s social self-perception (Domain 5) in pre-clinical years was significant greater than clinical years. In conclusion, this study identified strengths and areas for improvement of the educational environment at UTAR. UTAR medical students have positive perceptions on educational environment of UTAR. It was recommended that educational environment of UTAR related with social life of clinical year students should be monitored closely and maintain an educational environment that would satisfy for all MBBS students studying in UTAR.